2022
DOI: 10.1142/s0192415x22500239
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Effect of Icariin on Human Ovarian Cancer Cells via the NF-κB/PI3K-AKT Signaling Pathway: A Network Pharmacology-Directed Experimental Investigation

Abstract: Based on network pharmacology tools and public bioinformatics databases, the pharmacodynamic target and key mechanism of icariin (ICA) in the treatment of ovarian cancer (OC) were identified and experimentally verified. Our previous research showed that TNF, MMP9, STAT3, PIK3CA, ERBB2, MTOR, IL2, PTGS2, KDR and F2 are important targets of ICA in the treatment of OC. TNF, as a hub gene in tumor tissues, was associated with poor prognosis. ICA acted on OC mainly through the biological functions of various kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The results revealed that the therapeutic impact of ICA on AD may be implicated in a variety of signaling pathways including the PI3K-Akt signaling pathway, sphingolipid signaling pathway and NF-κB signaling pathway, consistent with previous studies [39]. In ovarian cancer, ICA has been proved to have a therapeutic effect via the PI3K-Akt signaling pathway and the NF-κB signaling pathway [40]. Consistent with the metabolomics results, ICA was speculated to affect the sphingolipid signaling pathway by PRKCA/TNF/TP53/AKT1/RELA/NFKB1 (Figure 6F).…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that the therapeutic impact of ICA on AD may be implicated in a variety of signaling pathways including the PI3K-Akt signaling pathway, sphingolipid signaling pathway and NF-κB signaling pathway, consistent with previous studies [39]. In ovarian cancer, ICA has been proved to have a therapeutic effect via the PI3K-Akt signaling pathway and the NF-κB signaling pathway [40]. Consistent with the metabolomics results, ICA was speculated to affect the sphingolipid signaling pathway by PRKCA/TNF/TP53/AKT1/RELA/NFKB1 (Figure 6F).…”
Section: Discussionsupporting
confidence: 90%
“…IκB is an inhibitor of NF‐κB, and inhibition of IκB can promote the activation of NF‐κB. NF‐κB is involved in the formation, invasion, metastasis, and angiogenesis of NSCLC (Gao et al., 2022). At the same time, it can affect the expression level of Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the therapeutic effect of ICA on AD may be mediated via a variety of signaling pathways, including the PI3K-Akt signaling pathway, sphingolipid signaling pathway, and NF-κB signaling pathway, consistent with previous studies [ 40 ]. ICA has been reported to have a therapeutic effect on ovarian cancer by regulating the PI3K-Akt signaling pathway and NF-κB signaling pathway [ 41 ]. Consistent with the metabolomics results, ICA was hypothesized to affect the sphingolipid signaling pathway via the PRKCA/TNF/TP53/AKT1/RELA/NFKB1 axis (Fig.…”
Section: Discussionmentioning
confidence: 99%